GEOLOGICAL AND GEOPHYSICAL CHARACTERISTICS OF THE ANABAR‐KHATANGA OIL AND GAS PROVINCE; NUMERICAL MODELING OF THE PROCESSES OF FORMATION OF SALT DOMES (SIBERIAN SECTOR OF THE RUSSIAN ARCTICS) - V. A. Kontorovich; В. V. Lunev; V. V. Lapkovsky (Геодинамика и тектонофизика, 2019)
The article discusses the geological structure, oil‐and‐gas‐bearing capacities and salt tectogenesis of the Anabar‐Khatanga saddle located on the Laptev Sea shore. In the study area, the platform sediments are represented by the 14‐45 km thick Neoproterozoic‐Mesozoic sedimentary complexes. The regional cross‐sections show the early and middle Devonian salt‐bearing strata and associated salt domes in the sedimentary cover, which may be indicative of potential hydrocarbon‐containing structures. Diapirs reaching the ground surface can be associated with structures capable of trapping hydrocarbons, and typical anticline structures can occur above the domes buried beneath the sediments. In our study, we used the algorithms and software packages developed by A.A. Trofimuk Institute of Petroleum Geology and Geophysics (IPGG SB RAS). Taking into account the structural geological features of the study area, we conducted numerical simulation of the formation of salt dome structures. According to the numerical models, contrasting domes that reached the ground surface began to form in the early Permian and developed most intensely in the Mesozoic, and the buried diapirs developed mainly in the late Cretaceous and Cenozoic.